2013
DOI: 10.2752/175303713x13636846944286
|View full text |Cite
|
Sign up to set email alerts
|

Walking Sole Mates: Dogs Motivating, Enabling and Supporting Guardians' Physical Activity

Abstract: Dog walking is receiving increasing attention in the public health literature as a strategy to improve dog guardians' physical activity levels. Quantitative research suggests that dog guardians walk more often and for longer than non dog-guardians, and offers suggestions as to the reasons for these differences. The purpose of this study was to qualitatively explore dog guardians' walking practices and relationships with their dogs, to better understand how and why dog walking might become an intervention point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 83 publications
1
24
0
4
Order By: Relevance
“…Our findings with identity and action control support this prior work. Qualitative interviews with dog owners highlight how dog walking is a duty or a role described with similarities to parenting children [50]. Further, Brown and Rhodes [13] found that a sense of dog responsibility/obligation was able to predict walking behavior independent of walking intention, which is similar to the results of the current study.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings with identity and action control support this prior work. Qualitative interviews with dog owners highlight how dog walking is a duty or a role described with similarities to parenting children [50]. Further, Brown and Rhodes [13] found that a sense of dog responsibility/obligation was able to predict walking behavior independent of walking intention, which is similar to the results of the current study.…”
Section: Discussionsupporting
confidence: 83%
“…Most research to date has been conducted in North America (e.g. [ 10 17 ]) or Australia (e.g. [ 18 23 ] with relatively limited data from the UK [ 9 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…And pets do matter to people. For instance, qualitative researchers have delved into positive as well as negative influences that urban dogs can have on wellbeing (Burrows et al ., ; Degeling & Rock, ; Degeling et al ., 2015; Derges et al ., ; Higgins et al ., ; Holmberg, 2013; Instone & Sweeney, ; McCormack et al ., ; Power, ; Power, ; Rock, 2017; Solomon, ; Tissot, ; Toohey & Rock, ; Urbanik & Morgan, ).…”
Section: Introductionmentioning
confidence: 99%